Targeting frustration: a review on reducing abnormal behaviors in broiler breeders via environmental enrichment - Quino, Marcela A.; Baker-Cook, Bethany (Frontiers in Ethology, 2026)
Broiler breeders are an essential component of broiler production, yet their welfare is compromised due to current management practices like feed restriction and housing conditions. These practices can lead to the development of abnormal behaviors, such repetitive pecking, feather licking, feather pecking, pacing, and polydipsia. Abnormal behaviors are indicative of poor welfare, and environmental enrichment is one potential strategy that can be used to reduce them. The impacts and use of environmental enrichment in broiler breeder production are an understudied field, and this review aims to identify potential environmental enrichment strategies that may mitigate abnormal behaviors in broiler breeders and highlight existing research gaps. The identified enrichments are pecking blocks, bales of substrate, perches, cover panels, and hanging pecking objects. These enrichments have been shown to address abnormal behaviors, encourage environmental complexity, and improve animal welfare. However, most of the enrichments proposed in this literature review need to be further studied to fully understand their impact on breeder behavior and welfare.